Tsetse wing pictures (Glossina sp.) from tsetse collected in protected and tsetse invested areas in Nigeria - Weber, Judith Sophie; Shaida, Stephen Saikiu; Ngomtcho, Sen Claudine Henriette; Musa, Usman Baba; Adamu, Ahmadu; Gbem, Thaddeus Terlumun; Berger, Petra; Mamman, Mohammed; Nok, Jonathan Andrew; Kelm, Sørge (In: Weber, JS et al. (2020): Molecular and morphological characterization of Glossina sp. and identification of associated Trypanosoma sp. in Nigeria including analysis for sialidase activity [dataset publication series]. PANGAEA, https://doi.org/10.1594/PANGAEA.915145, 2020)
This data set includes images of tsetse wings generated from a tsetse (Glossina sp.) collection carried out in Nigeria between 2014 and 2016. Traps were employed for one to three days in four different National Parks, one Game Reserve and two tsetse invested areas. Each tsetse was identified morphologically and dissected in the field. Selected tsetse wings were mounted in Faures' Solution and photographed to be used for morphometric analysis of wing size and relative vain distances. Species included are G. morsitans submorsitans, G. tachinoides, G. palpalis palpalis and some unidentified Glossina species.